2019
DOI: 10.3390/ijerph16030417
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Access to Sexual and Reproductive Health Services in Cameroon: A Mediation Analysis of the Role of Socioeconomic Factors

Abstract: There is growing evidence showing that people with disabilities face more frequently socioeconomic inequities than their non-disabled peers. This study aims to examine to what extent socioeconomic consequences of disability contribute to poorer access to sexual and reproductive health (SRH) services for Cameroonian with disabilities and how these outcomes vary with disabilities characteristics and gender. It uses data from a population-based survey conducted in 2015 in Yaounde, Cameroon. Mediation analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 40 publications
8
36
0
2
Order By: Relevance
“…Concerning the practice of HIV testing, only 23.2% of participants have ever been tested for HIV infections. In line with our finding, PWDs were less likely to be tested for HIV in Cameroon [ 3 ] and Uganda [ 24 ]. Similarly, as reported by previous research, families of PWDs may not encourage them to get HIV services [ 17 , 23 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Concerning the practice of HIV testing, only 23.2% of participants have ever been tested for HIV infections. In line with our finding, PWDs were less likely to be tested for HIV in Cameroon [ 3 ] and Uganda [ 24 ]. Similarly, as reported by previous research, families of PWDs may not encourage them to get HIV services [ 17 , 23 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…In Ethiopia, more than 15 million PWDs live with physical, sensory (hearing and visual loss), intellectual disabilities, or a combination of these disabilities [ 2 ]. The incidence of disabilities has been increasing due to accidents and the increase in chronic health conditions including HIV [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents the characteristics of the eligible studies. Of the 26 eligible studies, 19 were qualitative in design [7,10,11,[18][19][20][31][32][33][34][35][36][37][38][39][40][41][42][43]; four used a survey design [44][45][46][47]; and three used mixed methods design [48][49][50]. The 26 studies were reported from twelve African countries: Uganda (seven studies) [7,10,31,32,34,37,39];…”
Section: Study Characteristicsmentioning
confidence: 99%